Impact of oral condition on the quality of life of homeless people - Juliana Aparecida de Campos Lawder; Marcos André de Matos; João Batista de Souza; Maria do Carmo Matias Freire (Universidade de São Paulo, 2019)
ABSTRACT OBJECTIVE: To describe the prevalence of oral health impact on quality of life and its association with the dental condition and sociodemographic factors of homeless people. METHODS: The sample was composed of 116 adults, temporarily attended by a public institution in the municipality of Goiânia, state of Goiás. Interviews were carried out including the Oral Impact on Daily Performance instrument and sociodemographic aspects. Clinical examinations were done by a trained examiner considering criteria of the World Health Organization. We evaluated dental caries (DMFT index) and use or need to use some type of prosthesis. For the statistical analysis of data, we used Pearson's Chi-square and Fisher's exact tests and Poisson regression with robust variance. RESULTS: Of the total respondents, 81.9% had at least one daily performance affected by dental problems in the six months prior the survey. The most prevalent dental conditions were: need for lower arch (76.7%) and upper arch prosthesis (69.0%); untreated caries (75.9%); and high DMFT (57.8%). In bivariate analysis, only the need for upper prosthesis variable was associated with the impact (high Oral Impact on Daily Performance). In the regression model, adjusted for time in the institution, age, and sex, this association remained significant (p = 0.015). Individuals without need for upper prosthesis had prevalence of high impact on daily performance 55% lower than those in need of this type of prosthesis (p = 0.018). CONCLUSIONS: The prevalence of oral health impact on quality of life of homeless people was high and higher than that verified in the overall Brazilian population. The impact was associated with the need for upper prosthesis, regardless of sociodemographic characteristics of the individuals.